Effects of fulvic acid on growth performance, serum index, gut microbiota, and metabolites of Xianju yellow chicken - Feng, Peishi; Li, Qiaoqiao; Sun, Hanxue; Gao, Jinfeng; Ye, Xuan; Tao, Yi; Tian, Yong; Wang, Ping (Frontiers in Nutrition, 2022)
Fulvic acid (FA) is a mixture of polyphenolic acid compounds extracted from humus, peat, lignite, and aquatic environments; it is used in traditional medicine to treat digestive tract diseases. The purpose of the present study was to investigate the effect of FA on growth performance, inflammation, intestinal microbiota, and metabolites in Xianju yellow chicken. The 240 Xianju yellow chickens (age, 524 days) included were randomly categorized into 4 treatments with 6 replicates per treatment and 10 birds per replicate. Birds received a basal diet or a diet supplemented with 500, 1000, or 1500 mg/kg of FA, for a period of 42 days. Dietary supplementation of FA improved average daily gain (ADG) and feed conversion ratio (FCR) (P > 0.05). Compared with the control group, the serum level of TNF-α in birds supplemented with FA was significantly decreased (P < 0.05), and that of IL-2 was significantly increased after administration of 1500 mg/kg FA (P < 0.05). Analysis of gut microbiota indicated that FA reduced the relative abundance of genus Mucispirillum, Anaerofustis, and Campylobacter, but enriched genus Lachnoclostridium, Subdoligranulum, Sphaerochaeta, Oscillibacter, and Catenibacillus among others. Untargeted metabolomic analyses revealed that FA increased 7-sulfocholic acid, but reduced the levels of Taurochenodeoxycholate-7-sulfate, LysoPC 20:4(8Z,11Z,14Z,17Z), LysoPC 18:2, Phosphocholine and other 13 metabolites in the cecum. The results demonstrated that FA may potentially have a significant positive effect on the growth performance and immune function of Xianju yellow chicken through the modulation of the gut microbiota.